The Gambia - Joint World Bank-IMF Debt Sustainability Analysis - World Bank (World Bank, Washington, DC, 2019)
An updated DSA indicates that The Gambia is in external debt distress, though its public debt is deemed sustainable on a forward-looking basis. The external debt service-to-exports and -to-revenue ratios breach their indicative thresholds by large margins in the near term and signal major liquidity pressures. However, once these pressures are addressed by the prospective debt relief and the authorities’ fiscal consolidation and state-owned enterprise (SOE) reform program, the PV of total public debt would be brought below its threshold over the medium term. On the upside, debt relief discussions with external creditors are progressing and could unlock additional budget support. Downside risks mainly relate to the political environment and fiscal discipline, the unravelling of which could destabilize the economy and worsen the outlook for public debt.